Deposição de calda aplicada com aeronave remotamente pilotada nas culturas de milho e soja - Silva, Maria Rosa Alferes da (2022)
With the growing world demand for food production, new technologies have been used to increase productivity. In view of this, the use of remotely piloted aircraft (RPAs) for the application of phytosanitary products has grown. However, Brazil has little research data available regarding the efficiency and safety of this method. Therefore, the present work aimed to study the height and flight speed factors that influence the quality of the application of phytosanitary products with the use of RPAs, in corn (Zea mays L.) and soybean (Glycine max L.) , under Cerrado conditions. The spray deposition in the corn crop and the losses to the soil, promoted by the application, were evaluated using an RPA, at two flight heights (1.5 and 3.0 m) and a fixed speed of 21.8 km h -1, compared to the application with a backpack sprayer with a working speed of 5 km h-1 and height in relation to the crop of 0.5 m. And in the soybean crop, the spray deposition was evaluated, promoted by the application with RPA, at two flight speeds (15.4 and 21.8 km h-1) and fixed height in relation to the crop of 2.0 m, in comparison with the application with a backpack sprayer, in the upper and middle positions of the soybean plants. These evaluations were carried out through the detection of a tracer by spectrophotometry, and the coverage, density and spectrum of drops on water sensitive paper. It was found that the increase in flight height promoted a reduction in spray deposition and that the tested velocities did not influence the spectrum, coverage and droplet density.